Failure behaviours of friction stir spot welded joints of dissimilar ferrous alloys under quasi-static shear loads. (1st January 2014) - Hossain, Md. Abu Mowazzem; Hasan, Md. Tariqul; Hong, Sung-Tae; Miles, Michael; Cho, Hoon-Hwe; Han, Heung Nam
Joining process and failure behaviours of friction stir spot welded (FSSW) joints of two dissimilar ferrous alloys, cold rolled carbon steel (SPCC) and 409L stainless steel (SUS 409L), were investigated. Spot joints with four different material combinations were successfully fabricated by the FSSW process. The failure behaviours of the joints were investigated by quasi-static lap shear tests. Among the dissimilar material combinations tested, FSSW joints with the softer and more ductile material as an upper sheet (SPCC/SUS) provided better joint properties, including a slightly higher failure load and a significantly higher toughness, in comparison to having the softer material as the lower sheet. The different toughness properties of the SPCC/SUS and SUS/SPCC FSSW joints may be attributed to a dependency on the failure characteristic of the upper sheet material.